Disorder‐Induced Material‐Insensitive Optical Response in Plasmonic Nanostructures: Vibrant Structural Colors from Noble Metals. Issue 23 (30th April 2021) - Mao, Peng; Liu, Changxu; Niu, Yubiao; Qin, Yuyuan; Song, Fengqi; Han, Min; Palmer, Richard E.; Maier, Stefan A.; Zhang, Shuang
Abstract: Materials show various responses to incident light, owing to their unique dielectric functions. A well‐known example is the distinct colors displayed by metals, providing probably the simplest method to identify gold, silver, and bronze since ancient times. With the advancement of nanotechnology, optical structures with feature sizes smaller than the optical wavelength have been routinely achieved. In this regime, the optical response is also determined by the geometry of the nanostructures, inspiring flourishing progress in plasmonics, photonic crystals, and metamaterials. Nevertheless, the nature of the materials still plays a decisive role in light–matter interactions, and this material‐dependent optical response is widely accepted as a norm in nanophotonics. Here, a counterintuitive system—plasmonic nanostructures composed of different materials but exhibiting almost identical reflection—is proposed and realized. The geometric disorder embedded in the system overwhelms the contribution of the material properties to the electrodynamics. Both numerical simulations and experimental results provide concrete evidence of the insensitivity of the optical response to different plasmonic materials. The same optical response is preserved with various materials, providing great flexibility of freedom in material selection. As a result, the proposed configuration may shed light on novel applications ranging from Raman spectroscopy, photocatalysis, to nonlinear optics. Abstract : The optical response of materials, either at the macroscale or the nanoscale, is determined by their unique dielectric functions. Assisted by intrinsic disorder in fabrication, material‐insensitive reflection is achieved from plasmonic nanostructures composed of different noble metals. The disorder‐induced disentanglement between the optical response and the material properties may inspire novel applications ranging from photocatalysis to Raman spectroscopy.